Quantification of Organic richness through wireline logs: A case study of Roseneath shale formation, Cooper basin, Australia - Ahmad, M. (Institute of Physics Publishing, 2017)
The late Carboniferous-Middle Triassic, intracratonic Cooper basin in northeastern South Australia and southwestern Queensland is Australia's foremost onshore hydrocarbon producing region. The basin compromises Permian carbonaceous shale like lacustrine Roseneath and Murteree shale formation which is acting as source and reservoir rock. The source rock can be distinguished from non-source intervals by lower density, higher transit time, higher gamma ray values, higher porosity and resistivity with increasing organic content. In current dissertation we have attempted to compare the different empirical approaches based on density relation and Δ LogR method through three overlays of sonic/resistivity, neutron/resistivity and density/resistivity to quantify Total organic content (TOC) of Permian lacustrine Roseneath shale formation using open hole wireline log data (DEN, GR, CNL, LLD) of Encounter 1 well. The TOC calculated from fourteen density relations at depth interval between 3174.5-3369 meters is averaged 0.56 while TOC from sonic/resistivity, neutron/resistivity and density/resistivity yielded an average value of 3.84, 3.68, 4.40. The TOC from average of three overlay method is yielded to 3.98. According to geochemical report in PIRSA the Roseneath shale formation has TOC from 1 - 5 wt .There is unpromising correlations observed for calculated TOC from fourteen density relations and measured TOC on samples. The TOC from average value of three overlays using Δ LogR method showed good correlation with measured TOC on samples. © Published under licence by IOP Publishing Ltd.